2019
DOI: 10.3390/ma12040596
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Applications of Salt-Resistant Superabsorbent Poly (Acrylic Acid-Acrylamide/Fly Ash) Composite

Abstract: Solution polymerization synthesized alt-resistant superabsorbent poly (acrylic acid-acrylamide/fly ash) composites. The mass ratio of acrylic acid (AA) to acrylamide (AM), the concentration of crosslinker, the neutralization degree (ND) of AA, and the polymerization temperature were investigated by single-factor method. Optimized conditions for the synthesis of poly (acrylic acid-acrylamide/fly ash) (PAA-AM/FA) are, as following: m (AA)/m (AM) is 1.5, the content of crosslinker N, N-methylenebisacrylamide. (MB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 49 publications
0
13
0
Order By: Relevance
“…As a result, water entered the SAP structure, and SAP did not maintain a fixed shape. At a content of 0.04%, the three‐dimensional SAP network reached a balance between rigidity and flexibility, 38 thus, the water absorption capacity was observed to be the largest.…”
Section: Resultsmentioning
confidence: 99%
“…As a result, water entered the SAP structure, and SAP did not maintain a fixed shape. At a content of 0.04%, the three‐dimensional SAP network reached a balance between rigidity and flexibility, 38 thus, the water absorption capacity was observed to be the largest.…”
Section: Resultsmentioning
confidence: 99%
“…In curve b and curve c, the asymmetric stretching vibration peaks of -COO-at 1404 cm −1 and 1402 cm −1 can be observed, respectively; the stretching vibration absorption peak of sulfonic acid groups O=S at 627 cm −1 and 669 cm −1 , and the vibration absorption peaks at 1642 cm −1 and 1647 cm-1 were the stretching vibration peaks of C=O in the amide group [19,30], indicated that the polyacrylic acid chain and AMPS have been grafted onto the HEC skeleton. In the curve c, we found the Si-O-Si bending vibration peak of the laterite at 554 cm −1 [20], indicated that the laterite was involved in the polymerization reaction.…”
Section: Ftir Spectroscopymentioning
confidence: 88%
“…0.1 g sample under the optimum synthetic conditions was weighed and immersed in excess distilled water. Use a sieve to remove excess water at a set time interval (1,3,5,8,10,12,15,18,20,25,30,45,60,75,90,120,150,180, 210 and 240 min) and weighed it. The water absorption rate was calculated according to formula (1).…”
Section: Measurement Of Swelling Kineticsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mercury (II) ions in the environment mainly come from chlor alkali, battery manufacturing, chemical fertilizer, paper making, plastics, refining and paint industries [14,15]. The methods of mercury removal in water include chemical precipitation, coagulation, ion exchange, membrane filtration and adsorption [16,17]. Since most adsorption processes are exothermic and spontaneous.…”
Section: Introductionmentioning
confidence: 99%